Manajemen Stratejik Sebagai Proses Manajemen Keterdesakan - Kristamuljana, Sammy (International Research Journal of Business Studies, 2010)
Nowadays firms are being confronted with a very different kind of urgency situation than they have ever encountered before. The demand to maximize profit now comes along with a call for social responsibility and the effort to minimize the effect of the climate change. Still, there is not a single text-book on Strategic Management that mentions that the “urgency” management process is more appropriate than the “strategy” management process. Most of the textbook still identify Strategic Management with the strategy management process based on the uniformed steps: “Strategic Analysis, Strategy Formulation, Strategy Implementation, and Strategy Evaluation”. However, in reality, the number of firms that have failed to implement strategy keeps rising. To overcome the limitation of the strategy management process we need the urgency management process. Literature study has identified that there is urgency behind every strategy. The conducted case study research has succeeded in revealing the abovementioned urgency management process. The theory of urgency management process suggests that by managing the seven forces that generate the urgency the strategic leaders can generate the proven strategies to overcome the urgency.